Magnetic Outbreak Associated with Exploding Granulations - Jin, Chunlan; Zhou, Guiping; Ruan, Guiping; Baildon, T.; Cao, Wenda; Wang, Jingxiu (Astrophysical journal. Letters, 2023)
Diagnosing the spatiotemporal pattern of magnetic flux on the Sun is vital for understanding the origin of solar magnetism and activity. Here, we report a new form of flux appearance, magnetic outbreak, using observations with an extremely high spatial resolution of 0.″16 from the 1.6 m Goode Solar Telescope at the Big Bear Solar Observatory. Magnetic outbreak refers to an early growth of unipolar magnetic flux and its later explosion into fragments, in association with plasma upflow and exploding granulations; each individual fragment has flux of 10 16 –10 17 Mx, moving apart with a velocity of 0.5–2.2 km s −1 . The magnetic outbreak takes place in the hecto-Gauss region of pore moats. In this study, we identify six events of magnetic outbreak during 6 hr observations over an approximately 40″ × 40″ field of view. The newly discovered magnetic outbreak might be the first evidence of the long-anticipated convective blowup.